2018
DOI: 10.1016/j.apnr.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

“I was told that I would not die from heart failure”: Patient perceptions of prognosis communication

Abstract: This study shows that patients have different experiences and preferences for communication about prognosis and uses different approaches in order to cope living with a chronic illness such as heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
13
0
4
Order By: Relevance
“…However, this should not hinder nurses and physicians from communicating with relatives in a general way about treatment and care, their own situation and their support needs. For instance, both patients [74] and relatives [75] have reported that they prefer information about the expected course of the illness. However, healthcare professionals may feel uncomfortable about discussing end-of-life issues with patients and relatives because of feeling unprepared as well as worry about destroying hope [74,76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this should not hinder nurses and physicians from communicating with relatives in a general way about treatment and care, their own situation and their support needs. For instance, both patients [74] and relatives [75] have reported that they prefer information about the expected course of the illness. However, healthcare professionals may feel uncomfortable about discussing end-of-life issues with patients and relatives because of feeling unprepared as well as worry about destroying hope [74,76].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both patients [74] and relatives [75] have reported that they prefer information about the expected course of the illness. However, healthcare professionals may feel uncomfortable about discussing end-of-life issues with patients and relatives because of feeling unprepared as well as worry about destroying hope [74,76]. Nevertheless, in order to meet relatives' information needs, healthcare professionals should investigate what they can tell them about the patient's situation and what patients and relatives want to know.…”
Section: Discussionmentioning
confidence: 99%
“…A QPL needs to be used with care as patients have different approaches to cope with HF and also want different amounts of information depending on their current situation [ 7 ]. Some patients may only want to face part of the reality as a way of maintaining hope [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the amount of information about the HF trajectory wanted by the patient and the family member varies. Therefore, it is important for health care professionals to tailor their information according to the needs and preferences of each individual patient and family member [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a nationwide survey in Sweden, we found that communication about prognosis and end‐of‐life care does not seem to be routine in heart failure care and these discussions could be included more often . In interviews with patients with heart failure we also found that most patients want the health care professionals to be honest about the future and help the patient to be prepared for a time when heart failure is deteriorating …”
mentioning
confidence: 95%